Effects of professor swearing on learning and perceptions: a pilot field study - Washmuth, Nicholas B.; Stapleton, Karyn; Ballmann, Christopher G.; Caulkins, R. Mark (Frontiers in Education, 2025)
IntroductionThe purpose of this pilot study was to provide preliminary evidence on the effects of an instructor swearing during a lecture on learning and student perceptions in a field classroom setting.MethodsFirst-year doctoral students (n = 36) who were enrolled in a Human Anatomy course within a physical therapist education program were randomly assigned to a non-swearing lecture (NSL; n = 18) or a swearing lecture (SL; n = 18) on basic human anatomy. A single instructor provided identical 40-min lectures to each student group except for two inserted phrases to emphasize content which differed between NSL and SL. For the NSL, the instructor emphasized the content by stating: “Anatomy just makes sense sometimes” and “Anatomy is interesting.” For the SL, the content was emphasized by saying “Anatomy just makes f***ing sense sometimes” and “This s**t is interesting.” Following the lectures, a 10-question post-lecture knowledge retainment assessment (“pop” quiz) was given to the NSL and SL groups. The SL group also completed a 14-item mixed methods survey with 12 Likert and 2 open-ended questions regarding student perceptions.ResultsThere were no differences in knowledge retainment on the “pop” quiz scores between the NSL and SL (p = 0.780). Results from the mixed methods survey suggested an overall neutral to positive response to the SL whereby swearing did not negatively impact learning or perception of the instructor or the class.DiscussionCollectively, this pilot field study provides preliminary evidence suggesting that swearing during a lecture in higher education neither helps nor hurts student learning or perceptions of instructors and may positively impact student perceptions of the class. Future studies with additional control and larger diverse populations are warranted.